2021
DOI: 10.1186/s40842-020-00116-1
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting: is there a role in the treatment of diabetes? A review of the literature and guide for primary care physicians

Abstract: Background Type 2 Diabetes is a metabolic disorder characterized by hyperglycemia that causes numerous complications with significant long-term morbidity and mortality. The disorder is primarily due to insulin resistance particularly in liver, skeletal muscle, and adipose tissue. In this review, we detail the hormonal mechanisms leading to the development of diabetes and discuss whether intermittent fasting should be considered as an alternative, non-medicinal treatment option for patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 36 publications
0
57
0
6
Order By: Relevance
“…TR feeding is largely centered on the prolonged daily fasting period (14–16 h), which gives the body a chance to repair oxidative damage, leading to metabolic adaptations that sustain weight loss [ 55 , 56 ]. Fasting leads to decreased insulin production and reduced levels of insulin in the circulation [ 57 , 58 , 59 ] and also increases fatty acid utilization [ 60 ]. Fasting also forces a shift in metabolic pathway usage from a glucose-driven oxidative phosphorylation to ketone- and fatty acid-dependent metabolism [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…TR feeding is largely centered on the prolonged daily fasting period (14–16 h), which gives the body a chance to repair oxidative damage, leading to metabolic adaptations that sustain weight loss [ 55 , 56 ]. Fasting leads to decreased insulin production and reduced levels of insulin in the circulation [ 57 , 58 , 59 ] and also increases fatty acid utilization [ 60 ]. Fasting also forces a shift in metabolic pathway usage from a glucose-driven oxidative phosphorylation to ketone- and fatty acid-dependent metabolism [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, drugs all work by either increasing the endogenous production of insulin or increasing the amount of exogenous insulin received. While this works to reduce hyperglycemia in these patients, the concept of treating an insulin resistance disease by increasing insulin levels may be counterproductive, as it may later necessitate an increase in the dosage of medication over a long period of time (for review, please see: [ 13 ]). It appears that it is essential to find effective therapeutic solutions to treat obesity and diabetes and to reduce the spread of this pandemic of the 21st century.…”
Section: Obesity and Diabetes Mellitus: Epidemiology And Physiopathologymentioning
confidence: 99%
“…1 8 9 Exploring the mechanism behind IF TRE practices are increasing in popularity in the general population, with recent evidence supporting their use for diabetes and weight management in clinical populations under medical guidance. 3 These regimes have been shown to be well-tolerated, and lead to an average of 20% unintentional reduction in caloric intake. 10 It has been suggested that TRE may have additional benefits beyond calorie restriction, with several studies showing that these dietary patterns can improve insulin sensitivity and metabolic markers such as systolic blood pressure, HbA1c, fat mass and triglycerides, even in eucaloric conditions.…”
Section: Key Messagesmentioning
confidence: 99%
“…Emerging evidence shows IF has short and long-term benefits for health and exercise performance that go beyond facilitating weight-loss. [1][2][3][4] Despite its widespread use, there remains inconclusive evidence on how best to use IF for health and well-being. We discuss the emerging evidence related to IF and the potential for its use in personalised medicine.…”
Section: Introductionmentioning
confidence: 99%